NONLINEAR TIME HISTORY ANALYSIS AT 60 STOREY R.C. BUILDING USING DAMPED OUTRIGGER - Wilnando
The core-perimeter frame structure is a type of structure that is widely used for high-rise buildings. The results show that the majority of tall buildings above 250 m have an inherent attenuation ratio rate of less than 1% (Smith et al. 2010), which is not enough to eliminate input energy from excessive lateral forces, such as earthquakes. In this study, a comparison of outrigger structure to outrigger structure combined with damper will be carried out using a nonlinear analysis method of earthquake time history representing the city of Jakarta to identify the effectiveness of damping at outriggers. The presence of a damper can reduce the maximum drift value but cause more beams to yield. The performance of column elements and shear walls does not have much significant difference. The energy damping that is successfully damped by the damper is only 3% of the total even though it has used 82% of the existing force capacity